Lean production construction : prospects for the Icelandic construction industry - Christoph Merschbrock 1978- (2009)
The emerging concept of lean construction is concerned with the application of the lean paradigm to the construction industry. Purpose – This research paper seeks to identify the prospects and applicability of lean construction techniques at site level construction processes in the Icelandic construction industry. Design/methodology/approach – Firstly, the basis of current project management and tools to control construction in the Icelandic construction industry was identified through field observation at Iceland’s biggest contractor Ístak. Secondly, a project controls template aligned to the ‘Lean paradigm’ that could be used by the Icelandic construction industry was identified. This template was based on lean construction practice examples used by contractors outside of Iceland. Lastly, the likely acceptance amongst Icelandic construction companies of the project controls’ template and the appreciation of lean construction within the Icelandic construction industry were assessed. To get acquaintance of the aforementioned points, structured interviews featuring questionnaires as means for structured data collection were undertaken. These interviews were directed at a select number of senior project managers within the Icelandic construction industry. Findings – What became clear after having assessed what lean construction has to offer at site level is that construction controls aligned to the Lean paradigm seek to enhance production efficiency in the sense of a faster, more productive execution of single production tasks. It became also evident that these techniques require a significantly higher amount of planning work to prepare and ready the tasks. It became obvious that lean construction is not applicable to every construction setting and that JIT efficiency considerations can, especially in construction projects with significant variations and disruptive influences, cause difficulties with regards to project delivery. It became evident that some of the presently used project management practices are ...